2020
DOI: 10.3390/v12030338
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Ternary Interaction between NS1 of the 1918 Influenza A Virus, PI3K, and CRK

Abstract: The 1918 influenza A virus (IAV) caused the worst flu pandemic in human history. Non-structural protein 1 (NS1) is an important virulence factor of the 1918 IAV and antagonizes host antiviral immune responses. NS1 increases virulence by activating phosphoinositide 3-kinase (PI3K) via binding to the p85β subunit of PI3K. Intriguingly, unlike the NS1 of other human IAV strains, 1918 NS1 hijacks another host protein, CRK, to form a ternary complex with p85β, resulting in hyperactivation of PI3K. However, the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Considering the reasonably high ϕ-values of Y89 and D101, the specific binding orientation seems to be well-defined at the TS ( Supplementary Figure 2 ). Interestingly, we previously showed that the 1918NS1:p85β interaction is not significantly affected by a high salt concentration ( Dubrow et al, 2020 ). Although this seems contrasting with the result of D101A, the difference is reconciled by considering that the ϕ-value is a relative parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the reasonably high ϕ-values of Y89 and D101, the specific binding orientation seems to be well-defined at the TS ( Supplementary Figure 2 ). Interestingly, we previously showed that the 1918NS1:p85β interaction is not significantly affected by a high salt concentration ( Dubrow et al, 2020 ). Although this seems contrasting with the result of D101A, the difference is reconciled by considering that the ϕ-value is a relative parameter.…”
Section: Resultsmentioning
confidence: 99%
“…This is compatible with the X-ray crystal structure, as NS1 and p110 bind at opposite ends of p85. Additionally, NS1 proteins from some strains of influenza can form a heterotrimer with p85β and Crk proteins, discussed previously, in a manner that further enhances PI3K activation [ 133 , 198 ]. SH3 binding competent NS1 proteins were able to displace endogenous p85β-CrkL complexes and form a heterotrimer with NS1 as the bridge.…”
Section: Pi3kmentioning
confidence: 99%
“…We then sought to determine which viral protein is responsible for the stimulation of YAP/ TAZ activities. Since several literature has pointed out IAV NS1 could affect host cell signaling and control cellular processes such as activation of PI3K signaling [31,32], we hypothesized that that NS1 is responsible for the regulation of YAP/TAZ activities. Therefore, we transfected A549 cells with Flag tagged NS1 protein from PR8 virus, together with the luciferase reporter plasmids of CTGF or GTIIC.…”
Section: Iav Ns1 Binds To Yap/taz To Stimulate Their Activitiesmentioning
confidence: 99%